Clinical Evaluation of Sequential Transdermal Delivery of Vitamin B6, Compound Glycyrrhizin, Metronidazole, and Hyaluronic Acid Using Needle-Free Liquid Jet in Facial Seborrheic Dermatitis - Zhang, Xiaomin; Luo, Bizhu; Mo, Huihui; Liao, Lexi; Wang, Shuai; Du, Juan; Liu, Qiuting; Liang, Yanhua (Frontiers in Medicine, 2020)
Facial seborrheic dermatitis (FSD) is a common facial inflammatory dermatitis. Needle-free transdermal jet injection (NTJI) is a non-invasive injection of drug solution by using a high-pressure liquid injection instrument. To explore a safer, more tolerable, and convenient medical way using NTJI in the treatment of FSD, the patients were treated with vitamin B6, glycyrrhizin compound, metronidazole, and hyaluronic acid sequentially using NTJI every 2 weeks, and only those treated for more than three times were included. A VISIA facial imaging system for the evaluation of erythema, superficial lipid level, and roughness of skin surface and a CK analyzer for biophysical parameters, including the stratum corneum hydration, facial surface lipid, and trans-epidermal water loss, were applied. Erythema was significantly reduced after every treatment (weeks 2, 4, and 6; P < 0.05), whereas superficial lipid level was not improved significantly until week 6 (P < 0.05), and roughness of the skin surface was not improved significantly during the whole treatment. The stratum corneum hydration of lesional skin was significantly increased after three times of treatment (P < 0.05). No observable adverse effect, such as marked erythema, blistering, or atrophy, was observed. Sequential transdermal delivery of small molecular weight drugs (vitamin B6, glycyrrhizin compound, metronidazole, and hyaluronic acid) using NTJI is a safe, low-toxicity, and take-home drug-free therapy for the treatment of FSD.